Development of Dual-Layer Smart Coating Utilising Benzotriazole and Boiled Linseed Oil for Enhanced Pipeline Protection - Sitti Shalyza Qasidah Salleh; Muhammad Yasir; Puteri Sri Melor Megatt Yusof (Platform, a Journal of Engineering)
This study aims to develop and analyse the effect of single- and double-layer smart coating systems on enhancing the corrosion protection of carbon steel pipelines in oil and gas applications, addressing the challenge of corrosion in such harsh environments. Benzotriazole (BTA) is loaded into halloysite nanotubes (HNT) using a vacuum cyclic method to form BTA-HNT, and boiled linseed oil (BLO) is encapsulated within urea-formaldehyde microcapsules, referred to as MC-BLO. The double-layer smart coating (DLSC) is fabricated by mixing 15 wt% BTA-HNT and MC-BLO microcapsules with epoxy and applying it in two layers on carbon steel, while the single-layer smart coating (SLSC) with the same composition and total thickness is used for comparison. Characterisation techniques include Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FE-SEM), and energy-dispersive X-ray spectroscopy (EDX). Comparative electrochemical impedance spectroscopy (EIS) analysis reveals that DLSC offers superior corrosion resistance, increasing impedance from 4.75 Ω to 5.14 Ω after 14 days in a 3.5 wt% NaCl solution, indicating enhanced self-healing properties. Additionally, the adhesion strength of DLSC shows a minimal reduction of 31.07% after immersion, compared to 38.95% for SLSC and 52.08% for traditional epoxy coatings, highlighting the improved durability of the multilayer system. The superior performance of the DLSC is attributed to the efficient release of BTA and BLO in response to external stimuli. This study proposes DLSC as a novel strategy for developing high-performance self-healing coatings, demonstrating significant potential for improving corrosion protection in harsh environments.